1964
DOI: 10.1037/h0046613
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of student and professional prestige ranking of jobs in psychology.

Abstract: Granger (1959) demonstrated that psychologists perceive a prestige hierarchy of occupations in their own field. Tins study was an attempt to determine if the perception of the hierarchy was unique to psychologists. Granger's original questionnaire (consisting of 20 psychological occupations to be ranked according to prestige) was given to a sample of University students, who were grouped as "naive (N -111)" or "advanced (N = 73)" in terms ol psychulug.c.il training and identification with the field. The ranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1967
1967
1984
1984

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…High similarity of occupational prestige ranks assigned to a given list of occupations by different groups is an almost universal feature of occupational prestige research, some illustrative findings being those reported by Counts [3], Granger 151, and Porter and Cook [14]. Inkeles and Rossi [9] showed that this is an international phenomenon by comparing ranks for the same occupations reported in one study each conducted in Germany, Great Britain, Japan, New Zealand, USSR, and the United States.…”
Section: Discussionmentioning
confidence: 98%
“…High similarity of occupational prestige ranks assigned to a given list of occupations by different groups is an almost universal feature of occupational prestige research, some illustrative findings being those reported by Counts [3], Granger 151, and Porter and Cook [14]. Inkeles and Rossi [9] showed that this is an international phenomenon by comparing ranks for the same occupations reported in one study each conducted in Germany, Great Britain, Japan, New Zealand, USSR, and the United States.…”
Section: Discussionmentioning
confidence: 98%
“…Granger (1959) showed, for example, that a random sample of APA psychologists rated experimental psychologists as having more status than social, clinical, and counseling -psychologists. Porter and Cook (1964) extended Granger's work by comparing the ratings of undergraduate majors and nonmajors in psychology with those of Granger's sample of professional psychologists and found essentially, no differences in their rating patterns. Spearman rank-order correlations between median rankings of the jobs revealed associations of .…”
mentioning
confidence: 81%
“…The rankings by American Psychological Association (APA) members on Granger's (1959) questionnaire showed an occupational prestige hierarchy with respondents tending to upgrade occupations related to their specialty in psychology. Porter and Cook (1964) dichotomized University of Missouri subjects into 111 naive students taking their first course in psychology and 73 advanced students with at !The author was partially supported by a Rehabilitation Services Administration Traineeship. The research was conducted under the guidance of Robert G. Warnken.…”
mentioning
confidence: 99%